Answer:
The solution of the equation are x = - 1 , y = 0 and z = 3
Explanation:
Given three linear equation as :
6 x - y + z = - 3 ......A
4 x - 3 z = - 13 ......B
2 y + 5 z = 15 ......C
Solving eq A and C
I.e 2× (6 x - y + z ) = -3 ×2
or, 12 x - 2 y + 2 z = - 6
So, ( 12 x - 2 y + 2 z ) + ( 2 y + 5 z) = - 6 + 15
Or, 12 x + 7 z = 9 ......D
Solving eq B and D
I.e 3 × ( 4 x - 3 z ) = - 13 × 3
or, 12 x - 9 z = - 39
So, ( 12 x + 7 z ) - ( 12 x - 9 z ) = 9 + 39
or, 16 z = 48
∴ z =
![(48)/(16)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/in56js0axkuh4xdgiptg66n2wlbv4zzoaq.png)
i.e z = 3
put the value of z in eq D
So, 12 x + 7×3 = 9
Or, 12 x = 9 - 21
or, 12 x = - 12
∴ x = -
![(12)/(12)](https://img.qammunity.org/2020/formulas/mathematics/college/w94gpfulcuhw3gl59l2h6ek0ywqt5tmhxm.png)
I.e x = - 1
Now, Put The value of z in eq C
or, 2 y + 5 z = 15
or, 2 y + 5 × 3 = 15
Or, 2 y = 15 - 15
or, 2 y = 0
∴ y = 0
Hence The solution of the equation are x = - 1 , y = 0 and z = 3 Answer